Повышение эффективности воздействия модификаторов при электрошлаковом кокильном литье жаропрочных никелевых сплавов в транспортном машиностроении - Sergey Nikolaevich Zherebtsov; Evgeny Aleksandrovich Chernyshov; Alexander Aleksandrovich Alexandrov; Victor Ivanovich Gurdin (Вестник СибАДИ, 2017)
The results of the research, theoretical development and practical tests of products derived from the process of sharing and modification of high-temperature melt processing techniques (second) nickel alloys at electroslag chill casting, confirming the effectiveness of the technologies developed for improving the physical and mechanical properties of the product and service characteristics of the metal.